2017
DOI: 10.1088/1361-648x/aa6a76
|View full text |Cite
|
Sign up to set email alerts
|

Laser-induced ultrafast spin current pulses: a thermodynamic approach

Abstract: The ultrafast demagnetization process allows for the generation of femtosecond spin current pulses. Here, we present a thermodynamic model of the spin current generation process, based on the chemical potential gradients as the driving force for the spin current. We demonstrate that the laser-induced spin current can be estimated by an easy to understand diffusion model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 66 publications
(79 reference statements)
2
9
0
Order By: Relevance
“…The sign of the injected spin polarization for delay times fs is consistent with several theoretical predictions 20 22 , 36 . However, for delay times fs, several authors observed the injection of minority spins into the gold layer 18 , 21 .…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…The sign of the injected spin polarization for delay times fs is consistent with several theoretical predictions 20 22 , 36 . However, for delay times fs, several authors observed the injection of minority spins into the gold layer 18 , 21 .…”
Section: Resultssupporting
confidence: 88%
“…The detected majority polarization is in line with the super-diffusive model 13 as the majority electrons travel at a higher velocity. It is also in line with the thermodynamic model 36 as the chemical potential of the majority electrons is affected more by the heating pulse compared to the minority chemical potential. For all measurements, the rise time of the spin polarization is fs.…”
Section: Resultssupporting
confidence: 87%
“…First, a femtosecond laser pulse was used to generate spin currents perpendicular to the plane through the ultrafast spin Seebeck effect [ 7 ] and ultrafast superdiffusive spin currents. [ 8–18 ] By means of S2C, the spin current was converted into an in‐plane ultrashort charge current burst giving rise to the emission of THz electromagnetic waves. This scheme has enabled new applications such as spintronic emitters of ultrashort THz electromagnetic pulses.…”
Section: Figurementioning
confidence: 99%
“…All coupling constants are deduced from experimental results or first-principles considerations. This framework is intrinsically different from recent theoretical investigations of spin current generation [17], which employ a thermodynamic approach that assumes thermal equilibrium. In contrast, our approach is capable of dealing with the highly nonequilibrium scenarios that are expected to occur at such ultrafast time scales.…”
Section: Introductionmentioning
confidence: 98%